Kinematic Comparison and Description of the 3-Dimensional Shoulder Kinematics of 2 Shoulder Rotation Tests - Pascoal, Augusto Gil (2018)
Objectives: The purpose of this study was to compare shoulder external rotation range of motion (ROM) during the hand-behind-neck (HBN) test and a standard shoulder external rotation test and to describe the 3-dimensional scapular motion during the HBN test. Methods: An electromagnetic tracking device was used to assess the dominant shoulder of 14 healthy participants while performing active full ROM in a standard shoulder external rotation test in an elevated position (EREP) and in the HBN test. The humeral and scapular 3-dimensional positions at the end of EREP and HBN were compared using a paired-sample t test. A correlation analysis was performed between humeral and scapular angles to assess the contribution of scapular motion to the full shoulder ROM during the HBN test. Results: No significant differences were found between the HBN test and the EREP at the end-range of the glenohumeral external rotation (HBN: 15.6° ± 6.3° vs EREP: 23.4° ± 4.7°; P = .08) and on scapular internal-external rotation (HBN test: 21.2° ± 6.3° vs EREP: 15.6° ± 1.8°; P = .23). Significant differences were found in scapular upward rotation (HBN: 21.2° ± 6.3° vs EREP: 15.6° ± 1.8°; P b .01) and scapular spinal tilt (HBN: − 0.4° ± 2.3° vs EREP: 8.1° ± 2.1°; P b .01). There was a positive correlation between the humeral angles and scapular internal and posterior spinal tilt angles with the HBN test. Conclusions: The results of the present study showed that, in young asymptomatic participants with no known shoulder pathology, the end-range of shoulder rotation was similar in the HBN test and in a standard shoulder rotation test. During the HBN test, the scapula assumed a more internal and anterior spinal tilted position at the end-range of active shoulder external rotation. These results suggest that the HBN test may be used to assess the end-range of glenohumeral external rotation.